2016
DOI: 10.4070/kcj.2016.46.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan Reduces Lung Injury in a Canine Model of Cardiopulmonary Bypass

Abstract: Background and ObjectivesTo explore the lung-protective effect of levosimendan (LS) during cardiopulmonary bypass in a canine model by determining the wet/dry weight (W/D) ratio of lung tissue, malonaldehyde (MDA) and superoxide dismutase (SOD) concentrations, and performing a histological evaluation.Materials and MethodsThirty-two canines were divided randomly into four groups and underwent a routine aortic cross-clamping cardiopulmonary bypass procedure for 1 h, followed by recovery for 2 h. Animals were han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The administration of levosimendan exhibited a protective effect on lung function by reducing the duration of postoperative ventilation ( p = 0.007), although there was no significant difference in ICU stay ( p = 0.664) or in total hospital stay ( p = 0.405) between the two groups. Our findings align with experimental evidence supporting the lung-protective properties of levosimendan [ 15 , 16 ]. Studies by Landoni et al [ 1 ] and Lim et al [ 17 ] demonstrated a noteworthy reduction in hospital stay among patients treated with levosimendan.…”
Section: Discussionsupporting
confidence: 91%
“…The administration of levosimendan exhibited a protective effect on lung function by reducing the duration of postoperative ventilation ( p = 0.007), although there was no significant difference in ICU stay ( p = 0.664) or in total hospital stay ( p = 0.405) between the two groups. Our findings align with experimental evidence supporting the lung-protective properties of levosimendan [ 15 , 16 ]. Studies by Landoni et al [ 1 ] and Lim et al [ 17 ] demonstrated a noteworthy reduction in hospital stay among patients treated with levosimendan.…”
Section: Discussionsupporting
confidence: 91%
“…Diastolic dysfunction is a hemodynamic hallmark of heart failure. Many reports attempt to demonstrate the importance of early recognition of cardiac dysfunction by using echocardiography or other methods (Feng et al, 2016; Jang et al, 2016). While systolic function could be evaluated using echocardiography (such as ejection fraction, shortening fraction), the assessment of diastolic dysfunction (e.g., IVR time) by non-invasive method is challenging (Nagueh et al, 2009; Savage et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continuous improvement in different cardiac surgical techniques, the incidence of postoperative complications remains high. Such complications, which include POCD [19], acute lung injury [20], kidney injury [21], and intestinal injury [22], have become an important obstacle to the development of cardiac surgery. In this study, 6% hydroxyethyl starch was injected into Sprague-Dawley rats through the right venous drainage and right femoral artery fusion to establish a CPB model.…”
Section: Discussionmentioning
confidence: 99%